Measuring the Mathematical Representation Ability of Vocational High School Students in Solving Geometry Problems - Jumiarti, Jumiarti; Sukmawati, Sukmawati; Muzaini, Muhammad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The intent of this study is to measure and describe the mathematical representation ability of vocational high school students in solving geometry problems. Using a descriptive research design with a qualitative approach, this study evaluates three primary forms of representation: visual, symbolic, and verbal. The subjects were grade XI students at Vocational School 3 Pinrang, selected to represent different levels of visual-spatial intelligence to see how it affects their representational performance. Data was collected through mathematical representation tests and semi-structured interviews. The analysis followed the stages of data reduction, data display, and conclusion drawing. The findings indicate that students' mathematical representation abilities vary significantly. High-capacity students can present geometric problems visually, interpret symbols, and construct mathematical models, although they still struggle with verbalizing conclusions. In contrast, students with low ability are primarily limited to basic image-based tasks. The results show that while visual-spatial intelligence correlates with better representational skills, overall proficiency in solving complex geometry tasks remains low across the subjects. This measurement provides a baseline for developing targeted instructional strategies in vocational geometry education.